2016
DOI: 10.1039/c5dt04171f
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of fluoride salts by vasarenes: a key role of a self-assembled in situ dimeric entity via an exceptionally short [O–H–O] H-bond

Abstract: A self-assembled supramolecular dimeric entity via an exceptionally short (2.404 Å) and strong (22.9 kcal mol(-1)) [O-H-O](-) hydrogen bond is the key to the special reactivity of vasarenes with fluoride salts. Vasarene is a self-assembled, vase-shaped compound, obtained by the reaction between ninhydrin and phloroglucinol. Analogous compounds are prepared by replacing the phloroglucinol with other polyhydroxy aromatics. Vasarenes show special affinity towards compounds of the type M(+)F(-), where M being a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Among them, the shortest OÁ Á ÁO distances specified range from 2.457 Å (Barczyń ski et al, 2006), 2.446 Å (Pan et al, 1996), 2.437 Å (Polyakova et al, 1983) to 2.430 Å (Yang et al, 2010). However, a recent study in our group revealed a much shorter OÁ Á ÁO distance of 2.404 (3) Å when a completely different dimeric entity was formed in the reaction of (1) with tetramethylammonium fluoride (Bengiat et al, 2016).…”
Section: Database Surveymentioning
confidence: 78%
See 2 more Smart Citations
“…Among them, the shortest OÁ Á ÁO distances specified range from 2.457 Å (Barczyń ski et al, 2006), 2.446 Å (Pan et al, 1996), 2.437 Å (Polyakova et al, 1983) to 2.430 Å (Yang et al, 2010). However, a recent study in our group revealed a much shorter OÁ Á ÁO distance of 2.404 (3) Å when a completely different dimeric entity was formed in the reaction of (1) with tetramethylammonium fluoride (Bengiat et al, 2016).…”
Section: Database Surveymentioning
confidence: 78%
“…The supramolecular behaviors of these structures have been an ongoing study in our group, particularly their intriguing feature of selective affinity towards ion-pairs of type M + F À , M being a large monovalent cation (Almog et al, 2012). A recent study has shown that the multiple oxygen-containing functional groups of these ligands (hemiketals, carbonyls and hydroxyls) play a key role in this supramolecular binding mechanism by forming dimeric entities via strong [O-H-O] À hydrogen-bonding (Bengiat et al, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The question regarding the insolubility of the complex in water may be explained by considering: 1) The large size of the Cs + ions that is responsible for their low electrophilic properties; and 2) The lower hydration enthalpy, Δ H h °, of Cs + compared to that of the other alkali metal ions . The second can be regarded as a consequence of the first, as being the least electrophilic ion necessarily influences the ability to form multiple interactions with the water molecules.…”
Section: Figurementioning
confidence: 99%
“…The question regarding the insolubility of the complex in water may be explained by considering:1 )T he large size of the Cs + ions that is responsible fortheir low electrophilic properties; [17] and 2) The lower hydration enthalpy, DH h 8,o fC s + compared to that of the other alkali metal ions. [21] The second can be regardeda saconsequence of the first, as being the least electrophilic ion necessarily influences the ability to form multiple interactions with the water molecules. In addition, some studies on the hydrationo fa lkali ions have described Cs + as a" breaking-ion", [22] due to an unfavorable arrangement of the surrounding water molecules with regard to the intermolecular hydrogen bonding with each other,t hus, resulting in higher entropy.H ence, replacing the water molecules, which are involved in the solvation of the Cs + ,b yo ther interactions with [1] could be considereda se nergetically favorable in terms of both DH h 8 and DS h 8,l eadingt ot he formationo fa crystalline giant structure that precipitates from water.…”
mentioning
confidence: 99%